THE POTENCY OF TATAH SUNGGING SMES CREATIVE INDUSTRY IN SOLORAYA, CENTRAL JAVA, INDONESIA - Emi Widiyanti; Deny Tri Ardianto (Journal of Applied Economics in Developing Countries, 2016)
Small and Medium-sized Enterprises (SMEs) have shown their existence in overcoming the monetary crisis. SMEs have shown its contribution as well to local economy and labor absorption. One of creative industry SMEs is getting less attention. It is caused by being abandoned widely. However, it plays a very important part in maintaining the existence of nation culture is tatah sungging creative industry SME. Tatah sunggih is a part of wayang kulit (leather puppet) art recognized throughout the world as Indonesian original culture. This research aimed to explore the potency of tatah sungging creative industry in Soloraya area and to find out the characteristic of tatah sungging consumer currently. This study was a descriptive research taken place in Solo Raya areas including six regencies/cities: Solo, Boyolali, Sokoharjo, Wonogiri, Sragen, and Klaten. The data used was primary data taken from 30 respondents constituting the tatah sungging craftsmen that was then analyzed using descriptive analysis method. The result of research showed that 1) most craftsmen were 30-50 years old and had adequate education level, i.e. Senior High School or higher. Regarding experience, they had wrestled with this work for more than 10 years and it usually was inherited from one generation to the next. In one month, each SME could produce 5 pieces of leather puppet costing about IDR 1.5 millions per unit with volume sale of IDR 10 millions per month. Most of these SMEs had both local and regional market, and some had exported their product abroad; 2) the consumers of tatah sungging were mostly 30-40 years old with high education level, Senior High School or higher. Viewed from the type of occupation, the consumers of this industry were those working in the formal sector such as Civil Servants; it indicated that the consumers belonging to educated community category. Keywords : industrial potency, consumer, tatah sungging, wayang kulit, Soloraya